PERSONALITY TRAITS AS DETERMINANTS OF STRESS AMONG SECONDARY SCHOOL TEACHERS IN ANAMBRA STATE - Anene Mmaduakonam; Obi Ifeoma E. (European Scientific Journal, ESJ, 2015)
The purpose of this study is to find out whether personality traits such as achievement drive, high competitive tendency, high level of anxiety and self concept are determinants of occupational stress. The study was guided by four hypotheses. The population of the study covered all the 6,036 teachers in 265 public secondary schools in the state. The sample consisted of 1,000 teachers made up of 450 males and 550 females; drawn through multi-stage sampling technique. The instrument for the study was a structured questionnaire tagged ‘Personality Traits and Stress’ (PTS) which was duly validated. Mean and t–test were used for data analysis. The findings of the study revealed that teachers with high achievement drive exhibited a significantly higher level of stress than those with low achievement drive; teachers with high competitive tendency exhibited a significantly higher level of stress than those with low competitive tendency; teachers with high level of anxiety exhibit a significantly higher level of stress than those with low level of anxiety; teachers with a low self– concept exhibit a significantly higher level of stress than teachers with high self–concept. Based on the findings it was recommended among others that teachers should be exposed to stress management techniques through seminars and workshops.